KAJIAN MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA PADA PT. SUCOFINDO UNIT PELAYANAN DONDANG - , Adi Suroso, Yudi Sudarsono LCA. Robin Jonathan2 (EKONOMIA, 2016)
YUDI SUDARSONO, 2016. Study of Occupational Health and Safety Management at PT. SUCOFINDO Services Unit Dondang, under the guidance of Mr. LCA.Robin Jonathan and Adi Suroso. This study aims to determine the effect of applying occupational health and safety management system on the performance of employee at PT. SUCOFINDO Services Unit Dondang, as well as to find out the company's policy in improving Occupational Health and Safety Program. The study population were employees of PT. SUCOFINDO Services Unit Dondang totaling 72 people. Samples were taken as many as 42 employees were determined by random sampling technique (random sample). Data field research in the form of questionnaires and direct observations, as well as literature. The analysis model used is a simple linear regression, hypothesis testing using the tool t test, Correlation coefficient (r) is 0.820 bigger than r table 0,304 means that there are positive and significant relationship between variable implementation of occupational health and safety on the performance of employee of PT. SUCOFINDO Services Unit Dondang. The coefficient of determination (r2) of 0.672 means that the variable application of the occupational health and safety management system work has amounted to 67.20% influence on the performance of employee of PT. SUCOFINDO Services Unit Dondang, while the remaining 32.80% influenced by other variables that are not included in the this study. Result of t test, where t is obtained 9.051 with a standard error (significant) 5% greater than t table 1.684 means that the implementation of occupational health and safety management system very significant effect the performance of employee of PT. SUCOFINDO Services Unit Dondang.